Rancang Bangun Prototype Sistem Real Time Pendeteksi Pelanggar Zebra Cross Pada Traffic Light Dengan Menggunakan Arduino - Reza Ridlo Nugraha; Sabriansyah Rizqika Akbar; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
A lot of vehicles users nowadays especially in Indonesia can not be avoidable from a lot traffic violators on traffic light. Arduino microcontroller is a mini computer that can be used as a control system based on connected devices and Arduino used to build automatic system or security system. Therefore, the researcher will build a real time system prototype that can be used for detecting traffic violaton on traffic lights. System using the concept of laser security system to detect traffic violators, VC0706 camera modules to retrieve image data and using millis function to help multitask and scheduling on the systems to run in real time. In the results of its functionality testing, the system accomplishes its tasks of scheduling traffic, detecting traffic violator and activating the alarms. At the testing time measuring accuracy on the researcher system using millis, the system have a time average finishing the tasks in a one scheduling loop for 66.004 seconds based on its deadline 66 seconds and result of error percentage about 0.006%.